Research Progress on Catalpol as Treatment for Atherosclerosis - He, Lei; Zhao, Rusheng; Wang, Youheng; Liu, Huibing; Wang, Xuehui (Frontiers in Pharmacology, 2021)
Coronary atherosclerotic heart disease, cerebrovascular disease, and peripheral artery disease are common diseases with high morbidity and mortality rates and must be addressed. Their most frequent complications, including myocardial infarction and stroke, are caused by spontaneous thrombotic occlusion and are the most frequent cause of death worldwide. Atherosclerosis (AS) is the most widespread underlying pathological change for the above diseases. Therefore, drugs that interfere with this pathophysiological process must be incorporated in the treatment. Chinese traditional and herbal drugs can effectively treat AS. With the development of traditional Chinese medicine, the active ingredients in common Chinese medicinal materials must be thoroughly purified prior to their application in western medicine. Various proprietary Chinese medicine preparations with remarkable effects have been used in AS treatment. Catalpol, the active component of Rehmannia glutinosa, belongs to iridoid terpene and has anti-inflammatory, antioxidant, insulin resistance improvement, and other related effects. Several reviews have been conducted on this compound and its actions against osteoporosis, neurodegenerative diseases, Alzheimer's disease (AD), Parkinson's disease (PD) and diabetes and its complications. The current review focused on catalpol’s effect on atherosclerotic plaque formation in different animal models. The potential mechanisms of catalpol to ameliorate AS were also summarized in terms of oxidative stress, inflammation, cell aging, apoptosis, and activation of the silent information regulator factor 2-related enzyme 1 (SIRT1) pathway.